Fast strain mapping in abdominal aortic aneurysm wall reveals heterogeneous patterns - Bracco, Marta Irene; Broda, Magdalena; Lorenzen, Ulver Spangsberg; Florkow, Mateusz Cezary; Somphone, Oudom; Avril, Stephane; Biancolini, Marco Evangelos; Rouet, Laurence (Frontiers in Physiology, 2023)
Abdominal aortic aneurysm patients are regularly monitored to assess aneurysm development and risk of rupture. A preventive surgical procedure is recommended when the maximum aortic antero-posterior diameter, periodically assessed on two-dimensional abdominal ultrasound scans, reaches 5.5 mm. Although the maximum diameter criterion has limited ability to predict aneurysm rupture, no clinically relevant tool that could complement the current guidelines has so far emerged. In vivo cyclic strains in the aneurysm wall are related to the wall response to blood pressure pulse, and therefore they can be linked to wall mechanical properties, which in turn contribute to determine the risk of rupture. This work aimed at enabling biomechanical estimations in the aneurysm wall by providing a fast and semi-automatic method to post-process dynamic clinical ultrasound sequences and by mapping the cross-sectional strains on the B-mode image. Specifically, the Sparse Demons algorithm was employed to track the wall motion throughout multiple cardiac cycles. Then, the cyclic strains were mapped by means of radial basis function interpolation and differentiation. We applied our method to two-dimensional sequences from 8 patients. The automatic part of the analysis took under 1.5 minutes per cardiac cycle. The tracking method was validated against simulated ultrasound sequences, and a maximum root mean square error of 0.22 mm was found. The strain was calculated both with our method and with the established finite element method, and a very good agreement was found, with mean differences of one order of magnitude smaller than the image spatial resolution. Most patients exhibited a strain pattern that suggests interaction with the spine. To conclude, our method is a promising tool for investigating abdominal aortic aneurysm wall biomechanics as it can provide a fast and accurate measurement of the cyclic wall strains from clinical ultrasound sequences.